The Importance of Pre-Marriage Counseling Programs (Bimwin) for Prospective Couples Before Marriag - Nur Ainun; Sunuwati Sunuwati (IAIN Parepare, 2023)
The aim of this research is to investigate the implementation and significance of pre-marriage guidance for prospective couples before getting married at the Office of Religious Affairs (KUA) in Pancarijang District. The research methodology employed is descriptive with a qualitative approach. Data analysis relies on logical reasoning leading to general conclusions. Pre-marriage guidance is a program established by the Ministry of Religious Affairs and executed by the Office of Religious Affairs. The purpose of conducting this Pre-Marriage Guidance Program is to prepare prospective couples and acquaint them with the reality of married life that they will embark upon. Therefore, it is expected that prospective couples undergo this guidance before entering into marriage so that they are well-prepared and aware of the actualities of married life they will soon experience.